2001
DOI: 10.1023/a:1010603026913
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Duodenal HCO3- secretion increases in response to mucosal acidification by luminal acid. Although this process is known to be mediated by endogenous prostaglandins (PGs), the role of nitric oxide (NO) in this response has been little studied. We examined the effects of indomethacin and N(G)-nitro-L-arginine methyl ester (L-NAME) on the acid-induced HCO3- secretion in the rat duodenum, together with those on PGE2 generation as well as luminal release of NO metabolites (NOx). A proximal duodenal loop was perfuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These data indicate that cells expressing elements essential for HCO − 3 secretion and the TRPM5-positive cells represent two distinct populations and that in the proximal corpus mucosa apparently brush cells are not the source for secreted bicarbonate. However, the observation that TRPM5-positive cells were frequently located in close proximity to CFTR-stained cells might be of functional relevance, especially in view of the previous findings that in other tissues secretion of bicarbonate is strongly affected by neighboring cells using prostaglandin as paracrine signal (Flemström et al, 1982; Takeuchi et al, 1999; Sugamoto et al, 2001; Akiba and Kaunitz, 2009). If such a scenario was also realized at the “gastric groove,” the brush cells need to comprise the enzyme prostaglandin-endoperoxide synthase, also called cyclooxygenase (COX) [reviewed by Kim (2011)].…”
Section: Resultsmentioning
confidence: 87%
“…These data indicate that cells expressing elements essential for HCO − 3 secretion and the TRPM5-positive cells represent two distinct populations and that in the proximal corpus mucosa apparently brush cells are not the source for secreted bicarbonate. However, the observation that TRPM5-positive cells were frequently located in close proximity to CFTR-stained cells might be of functional relevance, especially in view of the previous findings that in other tissues secretion of bicarbonate is strongly affected by neighboring cells using prostaglandin as paracrine signal (Flemström et al, 1982; Takeuchi et al, 1999; Sugamoto et al, 2001; Akiba and Kaunitz, 2009). If such a scenario was also realized at the “gastric groove,” the brush cells need to comprise the enzyme prostaglandin-endoperoxide synthase, also called cyclooxygenase (COX) [reviewed by Kim (2011)].…”
Section: Resultsmentioning
confidence: 87%
“…Both mediators are capable of modulating mucosal blood flow, mucus and bicarbonate secretions, and the repair of mucosal injury [14, 32, 33]. Konturek et al [34]reported that the healing of gastric ulcers induced by acetic acid was delayed and promoted by administration of NOS inhibitors and L -arginine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although NO and PG affect acid-induced gastric mucosal hyperemia (45;46) and the gastric microcirculation (47), PG has no effect on the CRF 2 -mediated colonic hyperemia. Similarly, CRF 2 -mediated colonic hyperemia does not involve capsaicin-sensitive afferent fibers.…”
Section: Discussionmentioning
confidence: 99%